Diagnosis and Treatment of Influenza in Children - M. S. Savenkova (LLC "Diagnostics and Vaccines", 2016)
The article presents data on influenza epidemiology, pathogenesis, classification, clinical variants, diagnosis. Given the variety of antiviral drugs, highlighted the most relevant and used in pediatric patients, depending on age and mixed-flow options viral infections.